Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1016/j.resconrec.2020.105065
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus stocks and flows in an intensive livestock dominated food system

Abstract: Current use and management of phosphorus (P) in our food systems is considered unsustainable and considerable improvements in the efficiency of P use are required to mitigate the environmental impact of poor P stewardship. The inherent low P use efficiency of food production from animals means food systems dominated by livestock agriculture can pose unique challenges for improving P management. This paper presents the results of a substance flow analysis for P in the Northern Ireland (NI) food system for the y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 57 publications
0
29
0
1
Order By: Relevance
“…As the major consumer of P, the agricultural sector is key to understanding P sustainability, as it often dominates P stocks and flows (Rothwell et al, 2020). In this section, we examine changes in agricultural P use over the past 70 years, driven by increased pressure for efficient crop production, technological advancements, and niche innovations.…”
Section: Transitions In Us Agricultural Crop Phosphorus Use Efficiencymentioning
confidence: 99%
See 3 more Smart Citations
“…As the major consumer of P, the agricultural sector is key to understanding P sustainability, as it often dominates P stocks and flows (Rothwell et al, 2020). In this section, we examine changes in agricultural P use over the past 70 years, driven by increased pressure for efficient crop production, technological advancements, and niche innovations.…”
Section: Transitions In Us Agricultural Crop Phosphorus Use Efficiencymentioning
confidence: 99%
“…Transition shifts make P use efficiency a tool that requires a long-term perspective and global thinking beyond a one-dimensional assessment (Scholz & Wellmer, 2015). For example, when manure P is considered, it can provide a buffer against conventional P fertilizer shortages and price fluctuations, potentially reducing the vulnerability of livestock intense areas to shocks related to global P availability (Rothwell et al, 2020). Eventually, the P shocks on grain producing areas would be felt by the livestock areas, particularly those heavily reliant on imported feeds that are dependent on conventional P fertilizer (Rothwell et al, 2020).…”
Section: Transitions In Us Agricultural Crop Phosphorus Use Efficiencymentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have shown that P in Europe is sufficiently to abundantly available on agricultural lands [18]. This holds specifically true for agricultural businesses that have a surplus of organic fertilizers available, namely livestock-and biogas-based farms [19,20]. In many cases however, the abundant P is fixed by minerals and therefore not fully available for plants [21].…”
mentioning
confidence: 99%